CRIMEAN CONGO HEMORRHAGIC FEVER IN HAZARA DIVISION - Malik, Saqib; Diju, Inayat Ullah; Naz, Farhat (Journal of Ayub Medical College Abbottabad, 2011)
Background: Crimean-Congo Hemorrhagic fever (CCHF) is endemic in certain areas of Pakistan with 14 outbreaks in addition to many sporadic cases so far. It is highly fatal zoonotic disease caused by bite of infected tick. The objective of our study is to describe clinical features, treatment and outcome of CCHF positive cases during its outbreak in Hazara division, with the intention to bring focus to this fatal emerging disease. Methods: This study was conducted in Medical A Unit of Ayub Teaching Hospital, Abbottabad for a period of three months. All patients presenting with fever and platelet count less than 50,000/mm3 were included in the study. Apart from baseline investigations their blood samples were sent for the detection of CCHF virus. All patients were given supportive treatment including fresh frozen plasma and were started on oral Ribavirin. All patients were isolated and barrier personal precautions were observed by health care givers Results: Eighty-eight patients with fever and thrombocytopenia were included. Among these, 8 were found to be positive for CCHF. Supportive treatment with oral Ribavirin was given to all patients. One patient with CCHF died. One left against advice and six patients recovered completely. Conclusions: All patients presenting with acute fever and thrombocytopenia should be suspected and evaluated for CCHF. Oral Ribavirin is safe and effective in the treatment of CCHF. Keywords: Crimean Congo Hemorrhagic fever, Pakistan, Ribavirin